Recent Trends in Biotechnology Engineering: Innovations and Applications across Sectors - Dwivedi, Dinesh (AG Volumes, 2025)
The term "biotechnology" refers to biology-based technology that employs living things or their components to create or alter goods or enhance microbes, plants, and animals. From a global standpoint, biotechnology is the use of biological systems, creatures, or derivatives to create novel goods and procedures that improve people’s quality of life and solve global issues. Review the many studies on innovations, cross-sector applications, and current developments in biotechnology engineering that have been published in this article. This review highlight that recent advancements in biotechnology engineering have revolutionized multiple sectors, including medicine, agriculture, industry, and the environment. Innovations such as AI-driven automation, gene editing, bioprinting, and precision medicine are enhancing scalability, efficiency, and personalization of solutions. Startups are leveraging omics technologies, microfluidics, and additive manufacturing to develop cutting-edge applications. The integration of biotechnology with culturally relevant, inclusive healthcare models is crucial, especially in developing regions. Emphasizing decentralized healthcare and context-specific tools fosters equitable health outcomes. A holistic, interdisciplinary approach is essential to harness biotechnology’s full potential and ensure sustainable, accessible solutions across diverse global populations.